How prepared is the world? Identifying weaknesses in existing assessment frameworks for global health security through a One Health approach. Issue 10377 (25th February 2023) - Traore, Tieble; Shanks, Sarah; Haider, Najmul; Ahmed, Kanza; Jain, Vageesh; Rüegg, Simon R; Razavi, Ahmed; Kock, Richard; Erondu, Ngozi; Rahman-Shepherd, Afifah; Yavlinsky, Alexei; Mboera, Leonard; et al.
Summary: The COVID-19 pandemic has exposed faults in the way we assess preparedness and response capacities for public health emergencies. Existing frameworks are limited in scope, and do not sufficiently consider complex social, economic, political, regulatory, and ecological factors. One Health, through its focus on the links among humans, animals, and ecosystems, is a valuable approach through which existing assessment frameworks can be analysed and new ways forward proposed. Although in the past few years advances have been made in assessment tools such as the International Health Regulations Joint External Evaluation, a rapid and radical increase in ambition is required. To sufficiently account for the range of complex systems in which health emergencies occur, assessments should consider how problems are defined across stakeholders and the wider sociopolitical environments in which structures and institutions operate. Current frameworks do little to consider anthropogenic factors in disease emergence or address the full array of health security hazards across the social–ecological system. A complex and interdependent set of challenges threaten human, animal, and ecosystem health, and we cannot afford to overlook important contextual factors, or the determinants of these shared threats. Health security assessment frameworks should therefore ensure that the process undertaken to prioritise and build capacity adheres to core One Health principles and that interventions and outcomes are assessed in terms of added value, trade-offs, and cobenefits across human, animal, and environmental health systems.